2023
DOI: 10.1186/s13148-023-01481-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic effects of herbal medicine

Abstract: Epigenetic memory is essential for life that governs the predefined functional features of cells. Recent evidence has indicated that the epigenetic modification provides a potential link to gene expression changes that may be involved in the development of various chronic diseases, and targeting the epigenome becomes a plausible method for treating diseases. Traditional herbal medicine has gradually entered the vision of researchers due to its low toxicity and its effectiveness in treating diseases. As a matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…(a) DNA methylation and histone modifications: Advancements in research indicate that heavy metal exposure can instigate epigenetic alterations in medicinal plants. This phenomenon, manifested through DNA methylation and histone modifications, becomes a pivotal mechanism altering the expression patterns of genes associated with antioxidant systems within medicinal plants [ 144 , 145 ]. The regulatory influence of these epigenetic modifications extends beyond immediate responses, shaping the long-term adaptive trajectories of plants in the face of heavy metal stress [ 49 , 61 ].…”
Section: Heavy Metal Pollution Of the Environment And Concerns For Me...mentioning
confidence: 99%
“…(a) DNA methylation and histone modifications: Advancements in research indicate that heavy metal exposure can instigate epigenetic alterations in medicinal plants. This phenomenon, manifested through DNA methylation and histone modifications, becomes a pivotal mechanism altering the expression patterns of genes associated with antioxidant systems within medicinal plants [ 144 , 145 ]. The regulatory influence of these epigenetic modifications extends beyond immediate responses, shaping the long-term adaptive trajectories of plants in the face of heavy metal stress [ 49 , 61 ].…”
Section: Heavy Metal Pollution Of the Environment And Concerns For Me...mentioning
confidence: 99%
“…As another example, micronutriment supplementation is often used in the post-partum period in dairy cattle. Although one study did not evidence effects of supplementation with a commercially available supplement on maternal PBMC (Peripheral Blood Mononuclear Cell) methylation (Gasselin et al, 2020), caution should be applied when herbal supplements with unknown or known epigenetic effects (Bozkurt et al, 2012;Wu et al, 2023) are administered to animals during reproductive cycles (Cui et al, 2022;El-Zaher et al, 2021;Japheth et al, 2021).…”
Section: Otherenvironmentaleffec Ts: Aneedfore Valuati Onmentioning
confidence: 99%
“…Traditional herbal medicine has gained widespread acceptance as an essential alternative and supplementary medicine that benefits cancer patients . Many studies have found that traditional medicinal plants, when taken as adjuvant treatment with radiotherapy, immunotherapy or chemotherapy, can increase quality of life, lengthen survival time, lessen side effects, and boost therapeutic effects. Owing to its efficiency and lack of negative side effects, the vital medicinal plant Curcuma aromatica Salisb (Cur) has been extensively utilized in traditional medicine. Several studies have showed the beneficial anticancer benefits of Cur.…”
Section: Introductionmentioning
confidence: 99%